Sosialisasi Perawatan dan Pembuatan Face Shield bagi Tenaga Kesehatan - Nuzulia Khoiriyah; Sri Mulyono; Bagus Satrio Waluyo Poetro (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Face shield is one of the important PPE (Personal Protective Equipment) for health workers in health services in the era of the COVID-19 pandemic as it is today. The limited number of face shield will certainly hamper the health services provided by the hospital. This Community Services activity was carried out at RSI Sultan Agung and RSIGM Sultan Agung to provide training on making face shield independently and also maintenance, so that face shield is more durable and not easily damaged. The tool used is a 3D printer which is easy to operate. 3D Printing technology will produce solid objects, and not like printing a sheet of paper on a printer that is commonly used. Design 3D models using CAD software. This activity was attended by 80 participants. 91.25% of participants are interested in making their own face shields as an effort to meet the need for face shields From the Community Services activities, around 100 face shields were produced which were handed over to the hospital.